Pengembangan Keterampilan Menulis Reflektif Siswa Sekolah Dasar melalui Pohon Literasi - M. Ziyan Takhqiqi Arsyad (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2020)
Writing as initial literacy is a prerequisite for individual participation in the wider environment. Indonesian language learning in the 21st century not only teaches students how to master a set of skills, but also how to use them optimally. Low writing skills can hinder students' progress in learning. In SDN Percobaan 2, Malang City, students' writing tends to describe knowledge only and does not reflect what students experience or understand from their perspective. Seeing these problems, learning should be developed. The literacy tree is an alternative to developing students' writing skills in elementary schools. Based on these problems the purpose of this study is to describe the students' reflective writing skills developed using the literacy tree. This research uses a qualitative approach with document studies. The data source of this research is the results of student writing after going through writing training activities. The data in this study are text exposures that contain ideas and sequence structure of ideas. The data collection technique of this research used the documentation technique. The first finding students write the sequence of activities in seven branches of literacy trees. That is, students can write down seven activities that they have done. The second finding, students' reflective writing reflects ideas according to topic and impressions when doing learning activities.